Rising Popularity in Gig Economy: A Case Study from India - Baishali Pal (International Journal of Religious and Cultural Studies, 2021)
This article raises an issue of the rising popularity of gig economy in India. A market that is based on a fixed-term contract or that is paid per project by a company, third party, or online marketplace is referred to as the "gig economy". By employing a case study approach, this article highlights the impact of gig economy in India. The gig economy's impact at work is widespread and felt across industries. It has completely transformed how people are engaged at work and has resulted in a fundamental shift in the way our economy operates. While the gig economy offers enormous benefits to workers in terms of flexibility, employment, freedom, and so on, it also has a negative impact on the industry's working environment. In both the global and Indian contexts, it has advantages and disadvantages.